Local Vibration Influence of Anaerobic Capacity in Rowers - Ciekurs, Kalvis; Krauksts, Viesturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Whole body vibration is a worldwide innovation as a part of training method that helps athletes to regain the power and get ready for next training faster. However less attention is paid to local vibration where an isolated muscle or muscle group is stimulated by the use of a vibration device. For the reason to determine the effect of local vibration on anaerobic capacity of rowers, two research groups were assembled from the students of Murjāņi Sport Gymnasium (MSG) during the period of time from November 13, 2010 to March 20, 2011 - the experimental group (EG) and control group (CG). We manage tests with stationary Concept-II ergometer, EMG and goniometry before and after the sessions of local vibrations. After the local vibration sessions for experimental group, the anaerobic test results prove considerable increase on the stationary rowing ergometer Concept - II. As for the control group, there were no considerable increase observed. EMG proves considerable Triceps Brachii muscle activity improvement for the experimental group, yet the activity improvement was not observed for the control group.